A Digitally Programmable Active-RC Filter for On-Chip Portable Sensor Applications - Márquez Marzal, Alejandro; Medrano, Nicolás; Calvo, Belén; Martínez, Pedro A. (Jornada de Jóvenes Investigadores del I3A, 2017)
An enhanced digital tuning approach for RC-active circuits is presented. Simulations of a 12-bit CMOS second-order filter provide a 11.46-bit effective resolution to linearly control the frequency over three decades with THD